CD64-Neutrophil expression and stress metabolic patterns in early sepsis and severe traumatic brain injury in children - Fitrolaki, Diana-Michaela (BioMed Central, 2013)
BACKGROUND: Critical illness constitutes a serious derangement of metabolism. The aim of our study was to compare acute phase metabolic patterns in children with sepsis (S) or severe sepsis/septic shock (SS) to those with severe traumatic brain injury (TBI) and healthy controls (C) and to evaluate their relations to neutrophil, lymphocyte and monocyte expressions of CD64 and CD11b. METHODS: Sixty children were enrolled in the study. Forty-five children with systemic inflammatory response syndrome (SIRS) were classified into three groups: TBI (n = 15), S (n = 15), and SS (n = 15). C consisted of 15 non- SIRS patients undergoing screening tests for minor elective surgery. Blood samples were collected within 6 hours after admission for flow cytometry of neutrophil, lymphocyte and monocyte expression of CD64 and CD11b (n = 60). Procalcitonin (PCT), C-reactive protein (CRP), glucose, triglycerides (TG), total cholesterol (TC), high (HDL) or low-density-lipoproteins (LDL) were also determined in all groups, and repeated on day 2 and 3 in the 3 SIRS groups (n = 150). RESULTS: CRP, PCT and TG (p < 0.01) were significantly increased in S and SS compared to TBI and C; glucose did not differ among critically ill groups. Significantly lower were the levels of TC, LDL, and HDL in septic groups compared to C and to moderate changes in TBI (p < 0.0001) but only LDL differed between S and SS (p < 0.02). Among septic patients, PCT levels declined significantly (p < 0.02) with time, followed by parallel decrease of HDL (p < 0.03) and increase of TG (p < 0.02) in the SS group. Neutrophil CD64 (nCD64) expression was higher in patients with SS (81.2%) and S (78.8%) as compared to those with TBI (5.5%) or C (0.9%, p < 0.0001). nCD64 was positively related with CRP, PCT, glucose, and TG (p < 0.01) and negatively with TC, LDL, and HDL (p < 0.0001), but not with severity of illness, hematologic indices, length of stay or mechanical ventilation duration. CONCLUSIONS: In sepsis, the early stress-metabolic pattern is characterized by a high (nCD64, glucose, TG) - low (TC, HDL, LDL) combination in contrast to the moderate pattern of TBI in which only glucose increases combined with a moderate cholesterol - lipoprotein decrease. These early metabolic patterns persist the first 3 days of acute illness and are associated with the acute phase CD64 expression on neutrophils.